Pengaruh Perceived Value terhadap Customer Engagement Behavior di Pusat Kebugaran FitHub - Santosa, Derick Philander; Alam, Bryan Marcello; Widjojo, Handyanto; Istijanto, Istijanto (Kajian Branding Indonesia, 2025)
This study aims to replicate previous research regarding the value acquisition, value co-creation, and the impact of perceived organic grocerant value on customer engagement behavior through brand trust. Quantitative methods were used, data collection through online surveys using questionnaires. Another research proposal examines the influence of perceived value on customer engagement behavior at FitHub gyms with the goal of providing business insights, better decision making,and academic contributions. Hypothesis testing, development of research instruments, and ensuring valid and reliable sampling were important focuses of this research. This research also limits the research location to a certain area and focuses on a certain time period, so the findings may have limited relevance and cannot be generalized to other locations. However, from the findings of this research, it is important for managers to know how to increase customer engagement behavior because the results have a positive correlation with a person’s social side. Then, on the brand trust side, you can also pay attention to the social, emotional value and price value offered because there is a significant correlation value.